PENGARUH AGRESIVITAS PAJAK TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Empiris pada Perusahaan Non-keuangan yang Terdaftar di Bursa Efek Indonesia pada Tahun 2013-2016) - Stefanus Ganang Sakti Wijaya; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2017)
This study aims to examine the effect of tax aggressiveness on Corporate Social Responsibility (CSR) disclosure. Dependent variable in this study is CSR disclosure in the corporate’s sustainability reports. The independent variable in this study is tax aggressiveness, which is measured by effective tax rates (ETR). This study uses 5 control variables, they are corporate’s size, leverage, capital intensity, Return On Asset (ROA), and environmentally sensitive. This study is replicated from Lanis and Richardson’s research (2013). This study uses 62 non-financial corporates that listed on Indonesia Stock Exchange and published Sustainability Report based on GRI 4 between 2013-2016 as samples. The statistical test uses a model of Ordinary Least Square (OLS) regression. The results of this study find that tax aggressiveness has a positive and significant effect on CSR disclosure. Thus, tax aggressive corporations are likely to be more disclosing CSR. This evidence confirming legitimacy theory and stakeholder theory in the context of corporate tax aggressiveness. Moreover, leverage and environmentally sensitive also have significant positive effect on CSR disclosure as control variables.